2016
DOI: 10.1111/ajgw.12214
|View full text |Cite
|
Sign up to set email alerts
|

Geographical classification of Chinese Cabernet Sauvignon wines by data fusion of ultraviolet-visible and synchronous fluorescence spectroscopies: the combined use of multiple wavelength differences

Abstract: Background and Aims: We report the chemometric classification of commercial Chinese Cabernet Sauvignon dry red wines according to the winegrowing region based on the coupling of synchronous fluorescence (SF) and ultraviolet (UV)-visible (VIS) spectroscopies. Methods and Results: Total SF spectra at a wavelength difference (Δλ) of 10-150 nm with 10-nm intervals, UV spectra in the 240 to 380 nm range and VIS spectra in the 380-to 700-nm range were recorded. A simple classification model was constructed by princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…In comparison to other spectroscopic methods, however, UV-Vis spectroscopy provides a limited number of spectral features; therefore, it could be used as a screening approach with more sophisticated techniques being implemented for further analysis. In addition, the combination of other spectroscopic methods like IR and fluorescence with UV-Vis spectroscopy can improve the accuracy of classification models used for authentication by fusion of the datasets [22,23]. 1 SVM, support vector machine; PCA, principal component analysis; LDA, linear discriminant analysis; PLS-DA, partial least squaresdiscriminant analysis; SIMCA, soft independent modelling of class analogy; OPLS-DA, orthogonal projections to latent structures discriminant analysis.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other spectroscopic methods, however, UV-Vis spectroscopy provides a limited number of spectral features; therefore, it could be used as a screening approach with more sophisticated techniques being implemented for further analysis. In addition, the combination of other spectroscopic methods like IR and fluorescence with UV-Vis spectroscopy can improve the accuracy of classification models used for authentication by fusion of the datasets [22,23]. 1 SVM, support vector machine; PCA, principal component analysis; LDA, linear discriminant analysis; PLS-DA, partial least squaresdiscriminant analysis; SIMCA, soft independent modelling of class analogy; OPLS-DA, orthogonal projections to latent structures discriminant analysis.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…In comparison to other spectroscopic methods, however, UV–Vis spectroscopy provides a limited number of spectral features; therefore, it could be used as a screening approach with more sophisticated techniques being implemented for further analysis. In addition, the combination of other spectroscopic methods like IR and fluorescence with UV–Vis spectroscopy can improve the accuracy of classification models used for authentication by fusion of the datasets [ 22 , 23 ].…”
Section: Spectroscopic Techniques Applied In Wine Authenticationmentioning
confidence: 99%
“…Classification methods using fluorescence spectroscopy have been previously applied for wine varietal, vintage and origin authentication (Ranaweera et al, 2021b;Ranaweera et al, 2021c;Sádecká and Jakubíková, 2020;Suciu et al, 2019), which tends to yield similar or even better performance compared to other spectroscopic methods like UV-vis, near-infrared, mid-infrared, synchronous fluorescence, or Raman (Mandrile et al, 2016;Riovanto et al, 2011;Tan et al, 2016). Ultimately, studies involving spectrofluorometry and chemometrics have demonstrated the approach as a valid tool for authenticating wine, and along with the present work, highlight the extent to which this type of data can be used to understand important traits related to wine chemical and sensory properties.…”
Section: Classification Of Sensory Clusters Based On Spectrofluorometric Analysismentioning
confidence: 99%
“…Among the analytical techniques used to generate data of high quality, near- and mid-infrared spectroscopies have been widely used for the authentication of grappa and other spirits [ 9 , 10 ], wine vinegar [ 11 ], Mexican tequila [ 12 ], and beers [ 13 , 14 ]. In addition to vibrational data, other spectroscopies, such as UV–vis, excitation–emission fluorescence, and nuclear magnetic resonance, have also been suggested for different classification and characterization purposes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For fast, selective, and sensitive analyses, high-resolution mass spectrometry combined with flow injection analysis has offered new opportunities for red wine discrimination and classification [ 17 ].…”
Section: Introductionmentioning
confidence: 99%